Market Efficiency and Organizational Corruption: Study on the Impact on Shareholder Value - Renata Crosara Miari; José Marcos Carvalho de Mesquita; Daniel Jardim Pardini (BBR: Brazilian Business Review)
With this study, we e valuated the influence of disclosure of the involvement of organizations in corruption on creating value for shareholders. We chosen four companies that had their names linked to allegations of corruption in the past 10 years. An event study was used to ve rify if relevant information tends to be immediately reflected in stock prices. We selected 28 events for analysis and we observed negative and positive variations of the securities in relation to the market, in the days before the disclosure, as in most o f the 20 days after publication. However, in cumulative terms, there was a rise in prices over time, returning to levels near those observed before advertising the event. The results indicate that the market did not behave efficiently in this analyzed period.